Impact of globalization on the educational reality - Callalli Pimentel, Aldo (2014)
The following article approaches the effects of the impact of globalization on the educational reality in Peru. The analysis begins with a historical approach on globalization; immediately afterwards the repercussions in the educational context are evaluated, then there is a critique of the merchandizing of the educational process and finally there are some ideas for an educational national project in favour of the socioeconomic development of Peru.